Recent Trends and Advancements in Inventory Management - Dubey, Ankit; Kumar, R (EAI Endorsed Transactions on Scalable Information Systems, 2023)
In this paper, we categorise and critically evaluate the current modelling and analysis approaches and procedures created by researchers and scientists in inventory management systems across different sectors such as healthcare, supply chain, and routing problems. Furthermore, we discuss recent trends and advancements in inventory management systems that deal with shortage. Based on our literature review, we propose a comprehensive research structure that is appropriate in the current environment and helpful in future study directions.
Keywords: Inventory Management; Supply chain; Economic order quantity; EOQ